1982
DOI: 10.1128/iai.37.3.1285-1288.1982
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Resistance of Immunocompromised Mice by a Muramyl Dipeptide Analog

Abstract: L18-MDP(Ala), a synthetic derivative of muramyl dipeptide, enhanced resistance against Escherichia coli and Candida albicans infections in aged mice and younger adult mice whose defense mechanism(s) had been depressed by X-ray irradiation or by treatment with cyclophosphamide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Because WAM025 contains protein, N-acetylglucosamine, and phosphorus, constituting phosphomannan-protein complex(es) (2,10,15), while WNM consists of a simple polysaccharide with a very small amount of protein, it is suggested that the other components of WAM025 other than the mannan part may have an important role in evoking the protection against C. albicans infection in mice. WAM-025 should thus be a useful immunostimulant in the host-defense system of infected and tumor-bearing hosts, similar to several immunopotentiators (16,(18)(19)(20)23). The possible collaboration of other factors with infection-protecting activity and the effect of post-treatment with WAM025 on C. albicans infection remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Because WAM025 contains protein, N-acetylglucosamine, and phosphorus, constituting phosphomannan-protein complex(es) (2,10,15), while WNM consists of a simple polysaccharide with a very small amount of protein, it is suggested that the other components of WAM025 other than the mannan part may have an important role in evoking the protection against C. albicans infection in mice. WAM-025 should thus be a useful immunostimulant in the host-defense system of infected and tumor-bearing hosts, similar to several immunopotentiators (16,(18)(19)(20)23). The possible collaboration of other factors with infection-protecting activity and the effect of post-treatment with WAM025 on C. albicans infection remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The bands of C3 protein in sera of mice with PBS and those from mice with the adjuvant were illustrated on the upper and lower side of each agarose slit, respectively. complement systems might be involved in the resistance mechanisms of animals to microbial infections, which are stimulated by MDPs (6,14,15,22,23,25). To clarify its involvement in the enhancement of defense by MDP-Lys(L18) against microbial infections in mice, a quantitative and qualitative examination was made of serum C3 in mice treated with or without the adjuvant.…”
Section: Discussionmentioning
confidence: 99%
“…Muramyl dipeptide (MDP) and some of its analogs (MDPs) have been reported to enhance the nonspecific resistance of animals to microbial infections (6,14,15,22,23,25). Osada et al have recently found that polymorphonuclear leukocytes (PMNs) were activated in vitro and in vivo by an MDP analog, Nn-(N-acetyl-muramyl-L-alanyl-D-isoglutamine)-N'-stearoyl-Llysine [MDP-Lys(L18)] (24).…”
mentioning
confidence: 99%
“…The two molecules were also found to effectively limit infection of the opportunistic pathogen Cornyebacterium kutscheri in a cortisone‐mediated model of immunosuppression . Similarly, 6‐ O ‐stearoyl‐MDP enhanced host resistance against both E. coli and C. albicans infection in immunocompromised mice treated with either X‐ray irradiation or cyclophosphamide and limited P. aeruginosa ‐associated pneumonia in immunocompromised guinea pigs . Nonspecific protection was observed as well during viral infections.…”
Section: Peptidoglycan Metabolites and Adjuvanticitymentioning
confidence: 93%